Polynomials

Find the remainder when 3x5 + 2x4 – 3x3 – x2 + 2x + 2 is divided by x² – 1.

a) 2x + 3
b) 2x – 2
c) 4x + 6
d) 3
e) None

See our previous ‘Questions of the Day’:  

Quant Question Of The Day: 80
Quant Question Of The Day: 79

8 comments

  1. Replace x^2 by 1
    So, 3x^5 will become 3x
    2x^4 will become 2
    -3x^3 will become -3x
    -x^2 will become -1
    2x + 2 will remain as it is

    Add them to get 2x + 3

XHTML: You can use these tags: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>

Recent Forum Posts/Questions/Answers